Expansion Of Current Wi-Fi Implementation Through Energy Efficient Way (International Journal of Engineering and Computer Science, 2015)
In Present days WiFi provide easy access to internet through portable devices such as smartphones, tablets. This techniqueimplement the current WiFi implementation in the way to design that allow mobile devices to advertise and discover small chunk ofinformation in very energy efficient way. This is easily possible in the crowded environments. This mechanism is also known as energyefficient discovery in a WiFi network. Another way this is says implementation of current WiFi in driver level implementation.